2012
DOI: 10.1161/circinterventions.111.963215
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Treatment After Drug-Eluting Stent Failure

Abstract: Background-The optimal percutaneous treatment of drug-eluting stent (DES) in-stent restenosis (ISR) and the correlates for recurrent DES ISR remain unclear. Methods and Results-From 2003 to 2008, 563 patients presenting with recurrent symptoms of ischemia and angiographic ISR after DES implantation were included. Of these, 327 were treated with re-DES (58.1%), 132 underwent vascular brachytherapy (23.4%), and 104 were treated with conventional balloon angioplasty (18.5%). Variables associated with target lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The “late catch up” phenomenon has been used to describe late luminal loss due to intimal hyperplasia . This phenomenon is usually seen after 6 months to 1 year post‐ICBT, attributing to the high incidence of TVR . TVR rates have been reported to be as high as 5.8% per year at 5‐year follow‐up with one study showing no significant difference in TLR at 5‐year follow‐up between ICBT and DES …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The “late catch up” phenomenon has been used to describe late luminal loss due to intimal hyperplasia . This phenomenon is usually seen after 6 months to 1 year post‐ICBT, attributing to the high incidence of TVR . TVR rates have been reported to be as high as 5.8% per year at 5‐year follow‐up with one study showing no significant difference in TLR at 5‐year follow‐up between ICBT and DES …”
Section: Discussionmentioning
confidence: 99%
“…17 This phenomenon is usually seen after 6 months to 1 year post-ICBT, attributing to the high incidence of TVR. 17,18 TVR rates have been reported to be as high as 5.8% per year at 5-year follow-up with one study showing no significant difference in TLR at 5-year follow-up between ICBT and DES. 7,16 There have been many studies directly comparing DES and ICBT for treatment of BMS-ISR, most of which had ≤5-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel-coated balloon angioplasty is not inferior to paclitaxel-eluting stents for BMS restenosis [29]. In ISR after DES implantation, a couple of studies have been conducted [24,30,31]. It should be determined whether same or the other DES is more beneficial in preventing recurrence of ISR.…”
Section: Prevention and Management Of Very Late In-stent Restenosismentioning
confidence: 99%
“…Delayed endothelial healing renders the artery vulnerable to blood clot formation (thrombosis), which can abruptly obstruct blood flow and cause myocardial infarction [ 42 ]. Recent clinical trials in patients treated with drug-eluting stents (DES) confirm the failure of this cardiovascular treatment modality in a significant percentage of patients [ 43 ]. DES have been linked to severe risks of blood clots which could develop months or even years after the stent is implanted [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical investigations have concluded that approximately one out of every 200 patients who receive a DES will experience a blood clot between six months and four years after the stent is implanted. Prior studies of late stent thrombosis show that these blood clots lead to a major heart attack or death approximately 70% of the time, with a fatality rate of 30% to 45% [ 43 ].…”
Section: Introductionmentioning
confidence: 99%